SAT0124 Aortic stiffness and time to wave reflection are associated with left ventricular diastolic dysfunction measures in rheumatoid arthritis. (12th June 2018) - Millen, A. M.; Mokotedi, L.; Gunter, S.; Robinson, C.; Michel, F.; Woodiwiss, A. J.; Tsang, L.; Norton, G. R.; Dessein, P. H.
Abstract : Background: Patients with rheumatoid arthritis (RA) experience an increased frequency of heart failure with a preserved ejection fraction (HFpEF) (1). The treatment of HFpEF is currently suboptimal. Elucidation of the underlying pathophysiological mechanisms of HFpEF may provide potential targets for its management. Diastolic dysfunction often precedes the progression to HFpEF (2). Abnormalities in aortic function contribute to diastolic dysfunction in non-RA populations (3, 4). Objectives: The aim of this study was to determine whether impaired aortic function is associated with left ventricular diastolic dysfunction in RA. Methods: Arterial function was determined by applanation tonometry using SphygmoCor software and left ventricular diastolic function was assessed by echocardiography in 176 patients with RA. Markers of arterial function included carotid femoral pulse wave velocity (PWV), central systolic and pulse pressure, pulse pressure amplification and the magnitude and timing of the forward and reflected waves. Markers of diastolic function included the ratio of early-to-late transmitral blood flow velocity (E/A), the ratio of E to the mean of the lateral and septal wall myocardial tissue lengthening at the mitral annulus (e')(E/e') and the septal and lateral e'. Relationships of comprehensively evaluated arterial function with markers of LV diastolic function were determined in confounder adjusted multivariate regression models. Results: The timing of the forward (Ft) and reflected (Rt) waves were each associated with E/A (Ft: partial r=0.20, p=0.02; Rt: partial r=0.30, p=0.001) and Rt was further associated with lateral e' (partial r=0.36, p<0.0001) and septal e' (partial r=0.36, p<0.0001); PWV was associated with E/e' (partial r=0.18; p=0.03). Reflected wave timing was associated with two indices of impaired relaxation (E/A<0.8: OR (95% CI)=0.51 (0.29-0.91), p=0.01; lateral e'<10: OR (95% CI)=0.43 (0.26-0.71), p=0.001); PWV was associated with an increased left ventricular filling pressure (E/e'>12: OR (95% CI)=1.58 (1.04-2.38), p=0.03). Conclusions: Aortic stiffness and time to wave reflection are associated with increased filling pressure and impaired relaxation of the left ventricle, respectively. The development of diastolic dysfunction in RA may be partly mediated by changes in large artery function. References: [1] Davis JM, Roger VL, Crowson CS, et al. The presentation and outcome of heart failure in patients with rheumatoid arthritis differs from that in the general population. Arthritis Rheumatol 2008;58:2603-11. [2] Aurigemma GP, Gottdiener JS, Shemanski L, et al. Predictive value of systolic and diastolic function for incident congestive heart failure in the elderly: the cardiovascular health study. J Am Coll Cardiol 2001;37:1042-8. [3] Peterson VR, Woodiwiss AJ, Libhaber CD, et al. Cardiac diastolic dysfunction is associated with aortic wave reflection, but not stiffness in a predominantly young-to-middle-aged community sample. Am J Hypertens 2016;29:1148-57. [4] Cauwenberghs N, Knez J, Tikhonoff V, et al. Doppler indexes of left ventricular systolic and diastolic function in relation to the arterial stiffness in a general population. J Hypertens 2016;34:762-71. Disclosure of Interest: None declared